The effect of aerobics exercises in some fitness Health Care variables for the elderly from woman aged 50 - 60 years. - Talib, Muna; Hashim, Teba (Journal of Physical Education, 2015)
The problem with research in women neglect to exercise with age, which leads to a deterioration of their condition Health and Physical and thus an increase in their weight and accumulation of lipids in different parts of the body and the inability to move. Objective of this research is to prepare the exercises Aerobic and identify the impact of these exercises in some fitness Health variables for elderly aged 50-60 years, and represented the research sample of 16 participants from employees Baghdad University and was applied physical exercises developed by a researcher at the research sample, for three and 8 average of weekly training modules is equivalent to 24 training unit. These exercises are characterized by continuity and diversity and the thrill of using music and gradient from easy to difficult, and in accordance with the age of the sample. And researcher concluded that aerobic exercises low-intensity to the middle and we do to burn fat and thus reduce the weight and measurement of the oceans as well as the body and caused an improvement in the overall shape of the body and fitness in health elderly variables. Researcher recommended to increase the duration of the application of curriculum more than two months to ensure weight loss of more and also reduce the oceans body more measurements, as well as the need to use training programs low intensity to the middle and addressed to other variables, and the necessity of continuing the women after the age of fifty years to go to sports halls and participate in fitness programs to maintain weight and general health